Evaluation of the Tenax trap in the Sample Analysis at Mars instrument suite on the Curiosity rover as a potential hydrocarbon source for chlorinated organics detected in Gale Crater. Issue 8 (27th August 2015) - Miller, Kristen E.; Kotrc, Benjamin; Summons, Roger E.; Belmahdi, Imene; Buch, Arnaud; Eigenbrode, Jennifer L.; Freissinet, Caroline; Glavin, Daniel P.; Szopa, Cyril
Abstract: The Sample Analysis at Mars (SAM) instrument suite aboard Curiosity has detected chlorinated organic compounds in Martian sediment samples. The chlorine in these molecules is thought to derive from oxychlorine salts in Martian sediments, but the carbon source remains under investigation. To constrain possible carbon sources, we investigated how the composition and concentration of oxychlorine phases in solid samples affect organic molecules released from the Tenax traps on board SAM. We created Mars analogue soils by spiking olivine sand with calcium perchlorate, magnesium perchlorate, or ferric iron chloride and analyzed the volatiles generated during pyrolysis–gas chromatography–mass spectrometry using commercial instruments operated under SAM‐like conditions, with and without a Tenax trap. Benzoic acid, phthalic anhydride, high molecular weight aromatics, and chlorobenzenes are produced from the trap in response to volatiles released during Cl salt pyrolysis. Changes in composition or concentration of oxychlorine phases between samples could thus potentially produce an increase in chlorobenzene, as observed between samples from Rocknest and Cumberland. However, in our experiments benzoic acid, phthalic anhydride, and chlorobenzenes increase in proportion with the amount of HCl sent to the trap, while in Cumberland samples the chlorobenzene increase showed no corresponding increase in HCl. Based on our experiments, the Tenax trap is a possible source of the traces of chlorobenzene observed at Rocknest, John Klein, and Confidence Hills. The order‐of‐magnitude higher chlorobenzene abundances observed at Cumberland cannot be attributed to the Tenax trap. Furthermore, we found no evidence of significant trap degradation after hundreds of experiments with Cl salt‐containing analogue soils. Key Points: SAM‐like pyrolysis of Cl salts forms chlorobenzene, benzoic, and phthalic acid Chlorobenzene from Tenax and Cl salt volatiles reacting correlates with HCl On Mars, chlorobenzene does not correlate with HCl, so could be sample derived